Increased Incidence of Stunting Due to Pesticide Exposure in Agricultural Areas - Putri, Shafira Anindyah; Setyowati, Putri Sari Retno; Elizah, Putri Nur; Silvia, Mega; Kurniyawan, Enggal Hadi (Jurnal Bidan Mandiri, 2024)
Children who grow up in agricultural areas have a risk of experiencing stunting or developmental disorders due to exposure to pesticides, which can be one of the factors for stunting. This study aimed to determine the side effects of pesticide exposure on the incidence of stunting in agricultural areas. The method used in writing this research is a literature review using keywords on Google Scholar "Stunting," "Petani," AND "Pestisida" and on PubMed and ScienceDirect using the keywords "Stunting" AND "Farmer OR Agroindustry" AND "Pesticide." According to the data analysis of several studies, the results show that pesticide exposure can affect the synthesis and metabolism of thyroid hormones and affect child growth and development. Research also states that agricultural activities carried out by mothers who work as farmers have an impact on child growth and development. The conclusion is that pesticide exposure can increase the incidence of stunting in agricultural areas caused by a disrupted thyroid TSH receptor (TSH-r) so that TSH inhibits thyroid hormones. Nurses as educators have an essential role in raising awareness of the risk of stunting in agricultural areas and reducing pesticide exposure, as well as improving parenting and good nutrition for children in the community